Akurasi Metode Penilaian Konsumsi Pangan sebagai Pengukuran Asupan Mikronutrien pada Remaja: Scoping Review: Accuracy of Dietary Assessment Methods as a Measurement of Micronutrient Intake in Adolescents: Scoping Review - Simatupang, Abdul Malik; Dewi, Yulia Lanti Retno; Andayani, Tri Rejeki (Universitas Airlangga, 2024)
Background: Micronutrient deficiency, including iron, vitamin A, B-12 and folic acid, can cause anemia and harm adolescent health. Accurate dietary assessment methods is crucial to detect micronutrient deficiencies, but existing methods, have limitations, necessitating a review to identify the accurate methods for assessing micronutrient intake in adolescents. Objectives: To determine the accuracy of dietary assessment methods as suitable option for measuring micronutrient intake in adolescents. Methods: This study utilized the Preferred Reporting Items for Systematic Review and Meta-Analysis extension for Scoping Review (PRISMA-ScR) flowchart approach. Article were identified from ScienceDirect, PubMed, Scopus, Google Scholar. Articles were included if participants aged 10-19 years, published between 2014-2024, written in English/Indonesian, original research articles and studies related to validation of dietary assessment methods for micronutrient intake. The keywords were